OPTIMIZING THE COORDINATION SKILLS OF 12-YEAR-OLD TENNIS PLAYERS BY USING UNCONVENTIONAL (ADAPTED) TRAINING METHODS - MIRON, Florin; ŞTEFĂNESCU, Horea (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2018)
The modern tennis is characterized by the restructuring of training content in the context of great performance of nowadays sports. Latterly, tennis implies a specific background of players' skills, which includes, first of all, a multifaceted training, the manifestation of a great level of creation, tactical inventiveness that can only be expressed by individuals who have reached a high level of technical, physical and psychological abilities. The significance of physical training is unanimously acknowledged, as it is the support of the players' activity, which can use their technical-tactical and psychological possibilities during training sessions and competitions. Under these circumstances, the need to apply "unconventional" training methods and create appropriate drills to positively influence the performance capability is, from our point of view, an essential preoccupation of the motricity specialist. Current performance training cannot be anchored in definitive template shapes. REZUMAT. Optimizarea capacităților coordinative în jocul de tenis utilizând metode neconvenționale la copiii de 12 ani. Tenisul modern se caracterizează prin restructurarea conținutului pregătirii, în contextul amplificării spectacolului sportiv. Azi, tenisul presupune un fond specific de aptitudini ale jucătorilor, care include în primul rând o pregătire polivalentă, manifestarea unei mari libertăți de creație, de inventivitate tactică, ce nu poate fi exprimată decât de indivizii care au atins un înalt nivel de măiestrie tehnică, fizică si psihologică. Însemnătatea pregătirii fizice este unanim recunoscută, deoarece constituie suportul activității jucătorilor care astfel își pot valorifica posibilitățile tehnico-tactice si psihologice. În aceste condiții, necesitatea aplicării unor mijloace și metode de pregătire inedite, “neconvenționale” adecvate influențării pozitive a capacității de performanță, reprezintă din punctul nostru de vedere o preocupare esențială a specialistului din domeniul motricității. Cuvinte cheie: tenis de câmp, performanţă, capacitate coordinativă, mijloc nespecific.